The travel amenity pod / Wan Nuramalin Wan Hussin ... [et al.] - Wan Hussin, Wan Nuramalin; Nazri, Nur Alissya; Arifuddin, Muhammad Takbir; Yahya, Ahmad Fareez (2021)
Plastic waste is becoming an alarming concern around the world. In our daily life, plastic use has been very common, and it is inevitable while travelling. Beauty products, food and beverages and cooking necessities are some of the most used amenities by travelers that use plastic packaging. Due to this, many tourist destinations such as heritage sites, beaches and conservation areas are badly affected by the tremendous amount of plastic. Therefore, the main objective of The Travel Amenity Pod is to introduce a water-soluble travel amenities packaging that will help reduce the rate of plastic consumption made by travelers during a trip. The novelty of this product can be acknowledged as it comprises pre-measured travel amenities like sunscreen, lotion, hand sanitizer, shaving cream and personal care in a water-soluble pod that can dissolve in water after use. This product is made from Polyvinyl Alcohol (PVA) synthetic polymers that are proven non- toxic, biodegradable and water soluble. It is also an effort to create portable travel amenities in small size that does not take up large space especially for solo travelers or campers. With the existence of The Travel Amenity Pod, we believe that this product will be a game changer to the packaging industry as it has great potential to be commercialized as a sustainable product especially to eco-conscious tourists and suppliers.